Strategi Cool Japan yang Baru untuk Menyelamatkan Pertumbuhan Ekonomi dan Citra Populer Jepang di Era Digital - Auliawan, Althaf Gauhar; Ratna, Maharani Patria (Vocational College of Diponegoro University, 2024)
This study discusses “The New Cool Japan Strategy” announced by the Japanese government in June 2024. This strategy has outlined a comprehensive plan to expand and revitalize the existing Cool Japan initiative, which aims to promote the attractiveness of Japanese culture around the world, leading to economic growth. However, there are still problems in the existing Cool Japan that need to be addressed, such as the issue of inadequate support for creators, slow digitalization, and lack of targets set for Cool Japan as a whole. This study aims to analyze “The New Cool Japan Strategy” historically to understand more deeply how the Japanese government's efforts to save Japan's economic growth and popular image in the digital era. This study's method is historical research with literature study through a multidisciplinary approach, such as socio-cultural sciences and history. The results of this study show that maximizing the potential of cultural capitalism and soft power is a common way for the Japanese government to save Japan's economic growth and popular image in the digital era. In addition, the specific actions of the new Cool Japan strategy to face future challenges such as accelerating the PDCA cycle, digital transformation, enhancing creator support, addressing piracy, and strengthening public-private collaboration are expected to solve the previous problems and be well implemented.